Pembudidayaan Maggot untuk Olah Sampah Rumah di Desa Pasir Angin Kecamatan Mega Mendung, Bogor - Oktivasari, Prihatin; Sucita, I ketut; Kurniawan, Asep; Rosyidah, Anis (PT. Lancar Media Komunikasi, 2024)
The potential for waste in West Java is very large. The average amount of waste production in 27 districts/cities of West Java in 2023 will be 2200 tons per day. The largest waste composition based on type of waste is food waste, and the largest waste composition based on source is household waste. Therefore, household waste processing is increasingly being encouraged in Bogor Regency through community empowerment. Household waste can be managed using maggots. Maggot cultivation training by resource persons was carried out offline and was attended by 20 participants consisting of residents and village stakeholders. Maggot cultivation being developed is dry maggots, live maggots and maggot eggs. The PNJ Lecturer Team, which collaborates between ICT KBK IoT-network and KBK Civil Engineering construction management, is making efforts to develop knowledge of waste management by providing facilities to manage household waste using Maggot cultivation.